Multivalued Theta - monotone operators - Paredes Rojas, Edú (2018)
This article we give an introduction to the multivalued operators, we present a new concept of monotonicity, the theta - monoticity, Which is a generalization of all known types of monoticity, this theory is very useful, since it allows us to study properties for all types of monticity by analyzing only one type of them. We generalize under certain conditions theorems that were only in finite dimension to infinite dimensional Banach spaces. Finally we show an application to the sobreyectividad in dimension finite that can be used in the theory of semigroups and imposing restrictions can be tested in more general spaces.